Doença periodontal destrutiva não inflamatória: relato de caso - Ide, Cristiano Sasake [UNESP] (2015)
Non inflammatory destructive periodontal disease (NIDPD) is a severe destructive periodontal disease characterized by attachment loss and alveolar bone resorption but gingival inflammation and periodontal pocket formation are not common prominent features. Although unusual cases of non-inflammatory destructive periodontal disease are described, their pathogenesis remains unknown and open to be discussed. A unique NIDPD case was investigated to illustrate the disease characteristic and discuss the possible etiology and treatment